2018
DOI: 10.1101/345223
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

O-GlcNAc modification of oncogenic transcription factor Sox2 promotes protein stability and regulates self-renewal in pancreatic cancer

Abstract: Pancreatic cancer is among the 3rd leading cause of cancer related deaths in the United States along with a 5-year survival rate of 7%. The aggressive biology of the disease is responsible for such dismal outcome and is manifested by an increase in self-renewal capacity of the cancer cells, which leads to an increased rate of tumor-recurrence, contributing to poor prognosis. Transcription factor SOX2 maintains a critical balance between differentiation and “stemness” and is thus tightly regulated within a cell… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…This novel modulation of RNR activity through O-GlcNAcylation of RRM1 at T734 links glucose and nucleotide metabolism in cancer initiation. Interestingly, it was reported that O-GlcNAcylation of oncogenic transcription factor Sox2 in pancreatic cancer cells is responsible for tumor initiation (Nikita Sharma et al, 2018;Qian et al, 2018). It would be worthwhile to investigate whether O-GlcNAcylation of RRM1, similar to Sox2, has a significant impact on cancer initiation and progression in general.…”
Section: Discussionmentioning
confidence: 99%
“…This novel modulation of RNR activity through O-GlcNAcylation of RRM1 at T734 links glucose and nucleotide metabolism in cancer initiation. Interestingly, it was reported that O-GlcNAcylation of oncogenic transcription factor Sox2 in pancreatic cancer cells is responsible for tumor initiation (Nikita Sharma et al, 2018;Qian et al, 2018). It would be worthwhile to investigate whether O-GlcNAcylation of RRM1, similar to Sox2, has a significant impact on cancer initiation and progression in general.…”
Section: Discussionmentioning
confidence: 99%
“…When pancreatic cancer develops increased O-GlcNAcylation may block cancer cell apoptosis and lead to oncogenic activation of NF-κB signalling (66). Several proteins with defined roles in pancreatic cancer have been shown to be modified by O-GlcNAc including the heat shock protein HSP70 (67), the transcription factor Sp1 (68), the Wnt signalling proteins β-catenin and LRP6 (69), and more recently the transcription factor Sox2 that determines self-renewal in pancreatic cancer and is responsible for tumour initiation (70). Inhibiting O-GlcNAcylation can reduce pancreatic tumour growth and progression suggesting HBP is promising potential therapeutic target (66,71,72).…”
Section: The Hbp Pathwaymentioning
confidence: 99%
“…Further, since UDP-GlcNAc is used by O-GlcNAc transferase (OGT) to glycosylate and regulate a large number of oncogenic proteins (like Myc), inhibition of UDP-GlcNAc production will affect the survival of the cancer cells (31). Consistent with this, previous studies from our laboratory have shown that HBP-fueled UDP-GlcNAc synthesis can be used by OGT to drive tumor growth and self-renewal (32,33). Thus, HBP forms an integral metabolic node, inhibition of which will affect the tumor and its microenvironment alike.…”
Section: Introductionmentioning
confidence: 65%
“…These are dependent on the genes that regulate self-renewal. Our previous results (32) show that OGT, an enzyme dependent on UDP-GlcNAc and thus HBP, was instrumental in regulating self-renewal in pancreatic cancer via its effect on Sox2. Our results showed that inhibition of GFAT1, the rate-limiting enzyme of HBP, using siRNA resulted in inhibition of a number of self-renewal genes like Sox2, Oct4 and KLF4 in the pancreatic cancer cell lines MIA-PaCa2 and S2VP10 (Figure 2A).…”
Section: Gfat1 Contributed To Aggressive Biology Of Pancreatic Cancermentioning
confidence: 90%